Impact of different lighting configurations in energy consumption of glass doors multideck display cases - Heidinger, Gustavo Galdi (2014)
This paper reports the results of experimental tests performed in a glass doors multideck display case for medium temperature. This type of equipment considers a large reduction in the thermal load due the use of doors, however, a large part of the energy consumption is coming from the lighting. Experimental tests were performed with different types of lighting setup to measure the energy consumption and its consequent impact on the thermal load. The configurations tested were: fluorescent lamps and LED, both tested in horizontal (under the shelves) positioning and only LED were tested in vertical (next to the doors) positioning. Comparing with fluorescent lamps, experimental results show that LED illumination under the shelves reduces the direct energy consumption in 41% and the LED in vertical position results in 74% of energy economy. The illuminance depends on the position at which the measurement is made, LED illumination under the shelves results in a variation of -26 to +31% and LED in vertical position results in a variation of -50 to +422%. The LED illumination in vertical positioning is the best alternative to save energy and highlight the products exhibited.